Self-assembly with degenerate prototropy - Baruah, Pranjal K.; Gonnade, Rajesh G.; Phalgune, U. D.; Sanjayan, G. J. (Journal of Organic Chemistry, 2005)
This work describes a rational approach for addressing the prototropy-related problems in heterocycle-based self-assembling systems by the use of degenerate prototropy. As a proof of principle, the utility of degenerate prototropy is demonstrated herein by developing heterocycle-based AADD-type self-assembling modules that exist as ``single set of protameric pair (duplex)'' in both solution and solid states. These self-assembling modules are quickly accessible in good yield by reacting 2-amino-5,5-disubstituted-1H-pyrimidine-4,6-diones, available in one step by the condensation of (x,a-dialkyl malonates and free guanidine, with isocyanates. Evidence from NMR spectroscopy, ESI mass spectrometry, and single-crystal X-ray diffraction studies confirmed the formation of molecular duplexes. The effect of electronic repulsion in duplex formation is also investigated. Their ready synthetic accessibility, remarkably high propensity to crystal formation, and the novel property of degenerate prototropy would make these novel self-assembling molecules promising candidates for many proposed applications.

Enantioselective syntheses of (-)-pinellic acid, alpha- and beta-dimorphecolic acid - Baruah, Pranjal K.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Tetrahedron, 2007)
An efficient enantioselective convergent approach for the synthesis of (-)-pinellic acid 1, alpha- and beta- dimorphecolic acid (2 and 3) from 1,9-nonane diol is described. The synthetic strategy features Sharpless asymmetric hydroxylation, Sonogashira coupling and Birch reduction. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: asymmetric dihydroxylation; influenza; Sonogashira coupling

Enforcing periodic secondary structures in hybrid peptides: a novel hybrid foldamer containing periodic gamma-turn motifs - Baruah, Pranjal K.; Sreedevi, N. K.; Gonnade, Rajesh G.; Ravindranathan, Sapna; Damodaran, Krishnan; Hofmann, Hans-Joerg; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2007)
{This note describes the design, synthesis, and conformational studies of a novel hybrid foldamer that adopts a definite compact, three-dimensional structure determined by a combined effect of the special conformational properties of the foldamer constituents. The striking feature of this de novo designed foldamer is its ability to display periodic gamma-turn conformations stabilized by intramolecular hydrogen bonds. Conformational investigations by single-crystal X-ray studies, solution-state NMR, and ab initio MO theory at the HF/6-31G*
Keywords: ammonia-TPD; benzylation reaction; Ce-Al-MCM-41; Friedel-Crafts alkylation; pyridine-FrIR

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Bronsted-acid-mediated divergent reactions of betti bases with indoles: an approach to chromeno[2,3-b]indoles through intramolecular dehydrogenative C2-alkoxylation of indole - Deb, Mohit L.; Pegu, Choitanya Dev; Deka, Bhaskar; Dutta, Prantu; Kotmale, Amol S.; Baruah, Pranjal K. (European Journal of Organic Chemistry, 2016)
Divergent reactions of various 1-(aminoalkyl) naphthols and 2-(aminoalkyl) phenols (commonly known as Betti bases) with indoles under Bronsted acid catalysis is reported. With the reaction strategies, one can efficiently synthesize important indole derivatives such as 3-(alpha,alpha-diarylmethyl)indoles and chromeno[2,3-b]indoles. Furthermore, we disclose here a new C-C bond-cleavage reaction, in which naphthol and phenol behave as leaving groups to produce diarylmethanes. Inexpensive reagents such as p-toluenesulfonic acid monohydrate and molecular iodine are used to catalyze the reactions. No metal catalyst is required. The starting material of the reactions, Betti bases, are easily prepared from a three-component reaction of naphthol/phenol, aldehydes, and secondary amines. The mechanisms for the reactions are established through some control experiments. Quinone methide is the key intermediate for all the reactions reported herein.
Keywords: Betti bases; C-O bond formation; Dearylation; Fused-ring systems; nitrogen heterocycles